2008
DOI: 10.1021/tx700363s
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Inhibition of P450 3A4 as a Chemoprotective Mechanism against Aflatoxin B1-Induced Cytotoxicity with cis-Terpenones

Abstract: We recently reported the protective effect of 2-hydroxy- cis-terpenone (HCT) against aflatoxin B 1 (AFB1)-induced cytotoxicity in human HepG2 liver cells ( Zhou et al. Chem. Res. Toxicol. 2006, 19, 1415-1419 ); however, the mechanism was not clear. In this paper, the chemoprotective mechanism was investigated with liver microsomes and purified P450 3A4 enzyme. HCT showed effective inhibition of the metabolic conversion of AFB1 in liver microsomes at 40 microM, and more importantly, the inhibition of the carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…OHCT, like artemisinin, rapidly kills the early ring stage in vitro , suggesting that it could be used in combination with a slow-acting drug, such as chloroquine. The previous demonstrations that OHCT inhibits human liver cytochrome P450 3A4 [ 8 , 9 ] further suggests that it may reduce metabolism of anti-malarial compounds, such as artemisinin, that are metabolized by this enzyme [ 11 ], thus increasing the half-life and rendering them more effective. The inhibition of human liver cytochrome P450 3A4 by OHCT was shown to be mixed competitive inhibition indicating that OHCT was binding at a site different from the active site [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OHCT, like artemisinin, rapidly kills the early ring stage in vitro , suggesting that it could be used in combination with a slow-acting drug, such as chloroquine. The previous demonstrations that OHCT inhibits human liver cytochrome P450 3A4 [ 8 , 9 ] further suggests that it may reduce metabolism of anti-malarial compounds, such as artemisinin, that are metabolized by this enzyme [ 11 ], thus increasing the half-life and rendering them more effective. The inhibition of human liver cytochrome P450 3A4 by OHCT was shown to be mixed competitive inhibition indicating that OHCT was binding at a site different from the active site [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of HCT and OHCT was described previously [ 7 , 8 ]. It was previously shown that OHCT protects human liver cells against aflatoxin and inhibits activity of liver microsomal cytochrome P450 3A4 [ 9 ]. This enzyme not only activates toxins, such as aflatoxin [ 10 ], but also contributes to the degradation of anti-malarials, such as artemisinin, thus suggesting that OHCT might increase the half-life of current anti-malarials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospray ionization mass spectroscopy (ESI-MS) analysis was carried out with a Thermo Fisher TSQ Quantum Max Triple Stage Quadrupole mass spectrometer (MA, USA). Compound 1 was obtained as previously reported [23].…”
Section: Methodsmentioning
confidence: 99%
“…Doxorubicin was used as a comparison at a final concentration of 0.05, 0.1, 0.2, 0.5, 1.0 or 2.0 µM. After 72 h, MTT assay was carried out as reported [23]. The cell viability of each treatment was plotted with GraphPad Prism program, and IC 50 values were obtained using sigmoidal dose-response analysis provided by the software (version 4.00, GraphPad Software, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation